DINAMIKA POLITIK DALAM PEMBENTUKAN PERATURAN DESA PERSPEKTIF SIYASAH SYAR’IYYAH - Rani, Rani; Fatmawati, Fatmawati (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2022)
This study aims to find out how the political dynamics in the formation of village regulations in Datara Village, Tompobulu District, Gowa Regency. The research method used is field qualitative research. The results showed that Datara Village has a very good political development, it can be seen from the government management system that involves the community, including in the formation of village regulations. The mechanism for the formation of village regulations involving the community in a tiered manner starting from the hamlet level to the village level has been in line with the principles of the formation of laws and regulations. Community involvement in the process of forming village regulations through deliberations at the hamlet and village levels reflects the application of the concept of shura' as one of the decision-making mechanisms in the concept of siyasah syar'iyah.